QUALITY OF BALINESE BEEF PRODUCED BY PESANGGARAN SLAUGHTERHOUSE WITH ABIANSEMAL VILLAGE ABATTOIRS - Anak Agung Sagung Sandatsari Dewi; I Ketut Suada; I MAde Sukada (Buletin Veteriner Udayana, 2024)
The increasing demand for beef causes the intensity of cattle slaughter to increase. This makes the existence of slaughterhouses (RPH) and abattoirs (TPH) indispensable in supporting the availability of meat in an area. The purpose of this study was to determine the quality of Balinese beef in terms of subjective and objective tests and to determine the difference in the quality of Balinese beef produced by Pesanggaran slaughterhouses and Abiansemal Village of abattoirs. The samples used in this study were Balinese beef slaughtered at Pesanggaran slaughterhouses and Abiansemal Village abattoirs, at the silver side (M. biceps femoris) as much as 125 grams/head of 16 meat samples. Each sample was subjectively (color test, odor test, consistency test, and texture test) and objectively (pH test, water binding capacity test, and moisture content test) tested for physical quality. Subjective data was analyzed by Mann Whitney test and objective data was tested by T test (Independent). The results of the subjective data research with the Mann Whitney test obtained the results of the color test of Balinese beef produced by RPH Pesanggaran and TPH Abiansemal Village respectively 6.03 and 8.77, the odor test both had a score of 2, the consistency test had a score of 2.6 and 1.8, the texture test had a score of 2.43 and 1.38. While the T Test (Independent) test for objective data obtained the pH test results of 5.48 and 5.6, respectively, the water binding capacity test was 73.29% and 76.07%, and the water content test was 66.42% and 69.36%. It can be concluded that the quality of Balinese beef from Pesanggaran slaughterhouses and Abiansemal Village abattoirs is in good condition and suitable for consumption. In order to obtain ASUH meat products, it is recommended to carry out guidance on abattoirs in accordance with the standards for slaughtering animals at slaughterhouses.